Microbial Debromination of Polybrominated Diphenyl Ethers by Dehalococcoides-Containing Enrichment Culture - Zhao, Siyan; Fan, Siyan; He, Yide; Zhang, Yongjun (Frontiers in Microbiology, 2022)
Polybrominated diphenyl ethers (PBDEs), commonly used as flame retardants in a wide variety of consumer products, are emerging persistent pollutants and ubiquitously distributed in the environment. The lack of proper bacterial populations to detoxify these recalcitrant pollutants, in particular of higher brominated congeners, has confounded the attempts to bioremediate PBDE-contaminated sites. In this study, we report a Dehalococcoides-containing enrichment culture, PB, which completely debrominates 0.44 μM tetra-brominated diphenyl ether (BDE) 47 to diphenyl ether within 25 days (0.07 μM Br–/day) and extensively debrominates 62.4 ± 4.5% of 0.34 μM hepta-BDE 183 (0.006 μM Br–/day) with a predominant generation of penta- through tri-BDEs as well as small amounts of diphenyl ether within 120 days. Later, a marked acceleration rate (0.021 μM Br–/day) and more extensive debromination (87.7 ± 2.1%) of 0.38 μM hepta-BDE 183 was observed in the presence of 0.44 μM tetra-BDE 47, which is achieved via the faster growth rate of responsible bacterial populations on lower BDE-47 and debromination by expressed BDE-47 reductive dehalogenases. Therefore, the PB enrichment culture can serve as a potential candidate for in situ PBDE bioremediation since both BDE-47 and BDE-183 are dominant and representative BDE congeners and often coexist in contaminated sites.